Sistem Pendukung Keputusan Penerimaan Dosen Tetap Menerapkan Metode SAW - Dendy Frans Gunawan Hutagalung; Ebenezer Maston Sinaga (ADA Research Center, 2023)
Lecturers are educators at the university level, where there are various skills and experiences to create human resources as needed. However, the many criteria that exist for each lecturer with different grades make it difficult for a university to determine whether the lecturer is worthy of being accepted at the university or not. In accepting Permanent Lecturers, a Decision Support System is required. This Decision Support System is able to solve the problems faced. The method used in this research is the SAW Method. because it is able to solve an assessment problem with a model using priority values or weights that have been determined for each need. The result of this research is that Alternative A5 in the name of